General anesthesia with local infiltration reduces urine retention rate and prolongs analgesic effect than spinal anesthesia for hemorrhoidectomy - Lin, Chun-Yu; Liu, Yi-Chun; Chen, Jun-Peng; Hsu, Pei-Hsuan; Chang, Szu-Ling (Frontiers in Surgery, 2024)
Postoperative pain and complications are major concerns after a hemorrhoidectomy. Achieving deep anesthesia and lower postoperative complications is essential. However, information on the suitable anesthesia method for ambulatory hemorrhoidectomy is unknown. We aimed to examine whether general anesthesia plus local infiltration (GAL) results in lower complications and pain than spinal anesthesia (SA) after a hemorrhoidectomy. This retrospective single-center cohort study in a tertiary medical center in East Asia evaluated excisional hemorrhoidectomies performed from January 1, 2017 to March 31, 2023 using GAL or SA. Data on the six most common complications, including pain, constipation, acute urine retention (AUR), bleeding, nausea, and headache, were analyzed from medical records. Overall, 550 hemorrhoidectomies were included in the study: 220 in the GAL group and 330 in the SA group. Patients' characteristics were similar in both groups. The AUR rate was significantly lower in the GAL group than in the SA group (15.5% vs. 32.1%, P<0.001). Although the proportion of pain score ≥4 in the GAL group was not significantly lower than that in the SA group (36.2% vs. 39.8%, P=0.429), the pain score curve showed a stable trend. Overall, the rate of adverse effects was lower in the GAL group (56.9% vs. 67.4%, P=0.023). There was no difference in the rates of other complications and emergency department readmission rates between the GAL and SA groups. GAL has a lower urine retention rate and a longer analgesic effect in multiple hemorrhoidectomies. Therefore, GAL is an optimal anesthetic method for hemorrhoidectomy.